2022
DOI: 10.1101/2022.03.07.22271699
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Severity of maternal SARS-CoV-2 infection and perinatal outcomes during the Omicron variant dominant period: UK Obstetric Surveillance System national cohort study

Abstract: Objectives To describe the severity of maternal infection when the Omicron SARS-CoV-2 variant was dominant (15/12/21-14/01/22) and compare outcomes among groups with different vaccination status. Design Prospective cohort study Setting UK consultant-led maternity units … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
0
0
1
Order By: Relevance
“…Even if several previous studies estimate that the Omicron variant gives less severe forms [3,4,5] and announces the end of the pandemic [11,12,13], our study showed that COVID-19 persists and the risk of severe and complicated forms caused by this variant should never be underestimated [14], especially during pregnancy [15,16,17]. This study also showed the efficiency of the RNA vaccine against the Omicron variant.…”
Section: Discussioncontrasting
confidence: 44%
“…Even if several previous studies estimate that the Omicron variant gives less severe forms [3,4,5] and announces the end of the pandemic [11,12,13], our study showed that COVID-19 persists and the risk of severe and complicated forms caused by this variant should never be underestimated [14], especially during pregnancy [15,16,17]. This study also showed the efficiency of the RNA vaccine against the Omicron variant.…”
Section: Discussioncontrasting
confidence: 44%